Satysfakcja z terapii wziewnej wśród pacjentów z astmą oskrzelową = Satisfaction with inhaled therapy in patients with bronchial asthma - Iwona Czerwińska Pawluk; Katarzyna Dońka; Violetta Paździor (Kazimierz Wielki University, 2015)
Czerwińska Pawluk Iwona, Dońka Katarzyna, Paździor Violetta. Satysfakcja z terapii wziewnej wśród pacjentów z astmą oskrzelową = Satisfaction with inhaled therapy in patients with bronchial asthma. Journal of Education, Health and Sport. 2015;5(3):352-360. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.44831 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A352-360 https://pbn.nauka.gov.pl/works/696064 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.02.2015. Revised 18.03.2015. Accepted: 21.03.2015.   SATYSFAKCJA Z TERAPII WZIEWNEJ WŚRÓD PACJENTÓW Z ASTMĄ OSKRZELOWĄ SATISFACTION WITH INHALED THERAPY IN PATIENTS WITH BRONCHIAL ASTHMA   Iwona Czerwińska Pawluk Radomska Szkoła Wyższa, Wydział Nauk o Zdrowiu, Radom ul. 1905 roku Uniwersytecki Szpital Dziecięcy, Lublin. ul. Prof.. A. Gębali 6   Katarzyna Dońka Uniwersytet Medyczny w Lublinie, Katedra i Zakład Pielęgniarstwa Pediatrycznego   Violetta Paździor Uniwersytet Medyczny w Lublinie, Katedra i Zakład Pielęgniarstwa Pediatrycznego           Streszczenie W terapii astmy oskrzelowej podstawą uzyskania i utrzymania kontroli choroby jest stosowanie się pacjenta/ jego opiekunów do zaleceń lekarskich w zakresie farmakoterapii, w której czołowe miejsce zajmuje aerozoloterapia. Satysfakcja pacjenta / jego opiekunów z terapii wziewnej jest jednym z celów leczenia chorych na astmę oskrzelową. Jest ona kluczowym elementem warunkującym przestrzeganie zaleceń lekarskich. Stosowanie się do zaleceń terapeutycznych uzależnione jest od wielu czynników, które ogólnie dzieli się na: czynniki dotyczące pacjenta i jego zachowań, czynniki współistniejące ze schorzeniem,  czynniki związane z opieką zdrowotną, czynniki społeczne i ekonomiczne, czynniki warunkujące możliwości terapii. Wpływ na poczucie satysfakcji z terapii mają relacje lekarz - pacjent, edukacja pacjenta i jego opiekunów. Satysfakcja z aerozoloterapii pozostaje w związku z możliwością uzyskania i utrzymania dobrej kontroli astmy, co wpływa na poprawę funkcjonowania pacjenta/ jego opiekunów w życiu codziennym.   Słowa kluczowe: astma oskrzelowa, terapia wziewna, satysfakcja.   Abstract In the treatment of bronchial asthma basis for obtaining and maintaining control of the disease is the use of the patient / her caregivers to medical recommendations in the area of pharmacovigilance, which occupies a prominent place aerosoltherapy. Patient satisfaction / caretakers of inhalation therapy is one of the goals of treatment of patients with bronchial asthma. It is a key element for the adherence to medical recommendations. Adherence to treatment guidelines is dependent on many factors, which are generally divided into: factors relating to the patient and his behavior, factors coexisting with the disease, factors associated with health care, social and economic factors, factors determining treatment options. The impact on a sense of satisfaction with the care they have relationships doctor - patient, patient education and their caregivers. Satisfaction with aerosol is related to the ability to obtain and maintain good asthma control, which improves the functioning of the patient / caretakers in daily life.   Keywords: bronchial asthma, inhalation therapy, satisfaction.